Analisis Keefektifan Kalimat pada Teks Esai dalam Laman “Metafor.id” Edisi April 2024 sebagai Bahan Ajar Membaca Pemahaman - Aulia Yasmin; Fathan Iqbal ‘Afi; Intan Puspita Listyani; Shinta Widiawati; Syifa Rindi Sapitri; Asep Purwo Yudi Utomo; Arum Yuliya Lestari; Ristiani Ristiani (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The effectiveness of sentences has a very important influence on the quality of the content of a literary work. In writing essays, it is important to use effective sentences so that implied and explicit messages can be conveyed clearly and well. The purpose of this study was to determine the effectiveness of sentences in essay texts on the April 2024 Edition of the